(untitled) (Research, Society and Development, 2022)
The native seed market in Brazil is recent, requires organization, and its governance is important, to approve resources’ quality and origin from taken resources. Widely ranged, Enterolobium schomburgkii was chosen, to sign use of simple techniques to evaluate seeds production. For the assessment of initial growth (germination and emergency), packages of three different provenances seeds (Alta Floresta, Sinop and Xingu-Araguaia) were evaluated, in two environmental conditions (controlled/Mangelsdorf/30 °C and seedbed/open area/room temperature) and four dormancy breaks (CTEA18, CTEA4, ELX, EA18), four samples with 25 seeds, in factorial design. Variables as germination/plant growth and GSR were evaluated with non-parametrical tests. Provenances were different: germination/plant growth was affected by all studied characters; meanwhile GSR, except environment. Both these characters are applied to evaluate plant vigour, important information to packages availability; or else, bigger will be GSR, higher will be seed growth speed, more environmentally adaptable will be the seed pack. Concerning dormancy, ELX, although laborious, was more consistent than other techniques, factor connected to provenances, due to variability of species distribution. Considering its wide range, physical dormancy break by sandpaper scarification was efficient. Thus, new studies are needed, in order to ensure robustness to the currently known recommendations.